Solid sedimentation rates history of the southern african continental margins: Implications for the uplift history of the south african plateau - (:unkn) unknown (My University, 2020)
The Cretaceous and Cenozoic fill of the continental margins of southern Africa (South-East Atlantic and Agulhas Margins) contains a continuous record of sediment supplied from the South African Plateau for the past 134 million years. Estimates of solid sediment volumes deposited offshore were calculated from isopach maps and extrapolated vertical cross-sections derived from a large amount of industrial geophysical data. Solid phase volumes and accumulation rates were calculated for six epochs: Lower Cretaceous (134-113 Ma), Mid Cretaceous (113-93.5 Ma), Upper Cretaceous (93.5-81 Ma and 81-66 Ma), Paleogene (66-25 Ma), Neogene (25-0 Ma). Our new compilation demonstrates the existence of two periods of elevated flux. The most important one occurs in the late Cretaceous (93.5 to 66 Ma) and was synchronous with an acceleration of onshore denudation as shown by thermochronometric data. After a period of extremely low accumulation rate, the second phase of elevated flux started in the Oligocene (~30-25 Ma) until present-day. From these observations we suggest that the main phase of uplift of the South African Plateau took place during the Upper Cretaceous. Two mechanisms, namely uplift caused by lithospheric delamination or by dynamic topography caused by the continent moving over the African Superplume, are viable explanations for our observations. The more recent and lower amplitude episode of enhanced accumulation rates is likely to correspond to a second period of uplift, potentially associated with the onset of uplift and extension along the East African Rift System.
Keywords: African Research